WHAT IS BUSINESS? GARRY ALFONSIUS Bachelor of Science in Business Administration at Universal Institute of Professional Management UIPM Singapore - Garry Alfonsius (Universal Journal, 2021)
All of people know about business. A business is defined as an organization or enterprising entity engaged in commercial, industrial, or professional activities. Businesses can be for- profit entities or they can be non-profit organizations that operate to fulfill a charitable mission or further a social cause. The term "business" also refers to the organized efforts and activities of individuals to produce and sell goods and services for profit. Businesses range in scale from a sole proprietorship to an international corporation. Several lines of theory are engaged with understanding business administration including organizational behavior, organization theory, and strategic management.